Testing the effectiveness of vannamei shrimp shell chitosan extraction with variations of organic acids in the demineralization stage: Pengujian Efektivitas Ekstraksi Kitosan Kulit Udang Vannamei dengan Variasi Jenis Asam Organik dalam Tahapan Demineralisasi - Pravitri, Kartika Gemma; Naufali, Muhammad Nizhar; Hidayatullah, Arbi (JITIPARI, 2025)
Chitosan is a natural polysaccharide derived from chitin, commonly found in the shells of crustacean animals. The production of chitosan involves several stages: deproteinization, demineralization, and deacetylation, which require the use of acidic and alkaline solutions. This study aimed to evaluate the effectiveness of various types of organic acids and a natural acid source, Averrhoa bilimbi (bilimbi fruit) extract, in the chitosan extraction process from Vannamei shrimp shells. The study employed a completely randomized design with a single factor consisting of four acid treatments: acetic acid (AA), citric acid (CA), lactic acid (LA), and bilimbi fruit extract (BE), each replicated three times. The chitosan obtained from each treatment was analyzed for its chemical characteristics and mineral content, and the results were further analyzed using Principal Component Analysis (PCA). The best results were obtained from the citric acid treatment, which produced chitosan with a moisture content of 6.59%, a degree of deacetylation of 91.72%, ash content of 2.68%, and magnesium and calcium contents of 2.56 mg/100g and 0.15 mg/100g (dry basis), respectively. In contrast, the bilimbi extract treatment resulted in an ash content of 41.64%, with magnesium and calcium contents of 1456.52 mg/100g and 4.17 mg/100g (dry basis), indicating that the bilimbi fruit extract still has low demineralization effectiveness.